Between Decentralization and Recentralization: Conflicts in Intramunicipal and Intermunicipal Governance in Tokyo’s Shrinking Suburbs - Ohashi, Hiroaki (2022)
The suburban territory of Tokyo Metropolis, officially called the Tama Area, is experiencing path-dependent, multifaceted shrinkage in the sociodemographic, economic, and political and administrative (including fiscal) dimensions. The following two processes taking place in the opposite direction are at work: the political and administrative decentralization of authority and responsibility and the sociodemographic, economic, and fiscal recentralization (or reurbanization) of workplaces, residences, and municipal finance. Amid decentralization and recentralization, intramunicipal and intermunicipal conflicts, which are interrelated, are emerging in the lowest tier of government. We first explore intramunicipal disarrays of ideas and practices within a municipal government and subsequently investigate intermunicipal contradictions that are generating oscillations between unification and fragmentation among municipal governments. These two conflicts result in the failure to promote inclusive and geographically extensive intermunicipal cooperation only through the efforts of municipal governments. This failure partly stems from the path-dependency of Tokyo Metropolis incorporating past political and administrative separations at intrametropolitan and intrasuburban levels. Consequently, municipal governments face difficulty in building healthy relationships with upper-tier governments, civil society, and the market. In conclusion, we emphasize the importance of creating new forms of governance systems for promoting spatially wider and functionally integrated intermunicipal cooperation by combining physical and virtual environments, which respectively have geographically greater and lesser limitations, and by involving private and community actors. This creation requires both politically bottom-up and top-down approaches by exploiting the emerging sense of the increasingly intertwined future under suburban shrinkage and by consolidating intermunicipal cooperation activities that are fragmentally dispersed.